THE EFFECT OF GALLERY WALK STRATEGY ON READING COMPREHENSION OF THE SECOND YEAR STUDENTS OF SMP MUHAMMADIYAH 1 PEKANBARU - Nabila Jannati; Jismulatif Jismulatif; M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: The research was aimed to find out the effect of gallery walk strategy toward students reading comprehension of the second year students of SMP Muhammadiyah 1 Pekanbaru. The design of this research was quasi-experimental research with an experimental group and control group pre-test and post-test. These two groups were selected to be a sample by using cluster random sampling. The data were analyzed by using t-test formula. It was found that t-test score was 2.351 while the t-table was 2.001. Since t-test score was higher than t-table, it can be concluded that alternative hypothesis was accepted. It means that there is a significant effect of gallery walk strategy on reading comprehension of the second year students of SMP Muhammadiyah 1 Pekanbaru.Key Words: Reading, Reading Comprehension, Gallery Walk